Olanzapine for chemotherapy-induced nausea and vomiting: systematic review and meta-analysis - Chelkeba L; Gidey K; Mamo A; Yohannes B; Matso T; Melaku T. (Pharmacy Practice, 2017)
Background: Chemotherapy induced nausea and vomiting (CINV) remains the most distressing event in patients receiving highly emetogenic chemotherapy (HEC) or moderately emetogenic chemotherapy (MEC). Objective: Therefore, this meta-analysis was conducted to evaluate the efficacy of olanzapine containing regimen in preventing acute, delayed and overall phases of CINV. Methods: PubMed, EBSCO, and Cochrane central register of controlled trials electronic databases were searched to identify RCTs that compared the effects of olanzapine with non-olanzapine regimen in preventing CINV. Randomized clinical trials (RCTs) that compared olanzapine containing regimen with non-olanzapine regimen were included. The primary outcomes were the percentage of patients achieving no vomiting or no nausea in acute, delayed and overall phases. Results: 13 RCTs that enrolled 1686 participants were included in this meta-analysis. 852 patients were assigned to olanzapine and 834 patients were assigned to non-olanzapine regimen (other standard antiemetic regimen). The percentages of no emesis achieved were 87.5%, 76.2%, 73.6% in olanzapine versus 76.7%, 61.8%, and 56.4% in non-olanzapine regimen in acute, delayed and overall phases, respectively. The percentages of no nausea were 82%, 64.3%, 61.6% in olanzapine group versus 71.3%, 41.8%, and 40.6% in non-olanzapine group in acute, delayed and overall phases, respectively. In general, olanzapine containing regimen achieved statistical superiority to non-olanzapine regimen in no vomiting endpoint in acute phase (OR 2.16; 95%CI 1.60 to 2.91, p<0.00001; I-square=5%; p=0.40), delayed phase (OR 2.28; 95%CI 1.1.46 to 3.54, p=0.0003; I-square=65%; p=0.001) and overall phase (OR 2.48; 95%CI 1.59 to 3.86, p<0.0001; I-square=69%; p< 0.0001). Conclusion: The current meta-analysis showed that olanzapine was statistically and clinically superior to non-olanzapine regimen in preventing CINV in most domains of the parameters.